KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN PEMBUATAN AKTA KELAHIRAN PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN DELI SERDANG - Nainggolan, Monica P.; Sadad, Abdul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Population Administration Service is part of the local government obligatory functions carried out by Department of Population and Civil Registry. Department of Population and Civil Registry has the task of providing services arrangement of birth certificate regulated in accordance with Law No. 23 Year 2006 concerning Population Administration, Deli Serdang is a district which has big population that it has a wide range of population issues.The study aims to determine the role of the Department of Population and Civil Registry in providing administrative services population, especially in the maintenance of a birth certificate in Deli Serdang district as well as to identify factors that affect the role of the Departmnent of Population and Civil Registry.This research uses descriptive method and qualitative data analysis. As for the informants in this study consisted of key informants: the Secretary, Head of Civil Registration Service, the Head of Birth and Death Section, Officer of Birth and Death Section and Society. Key informants are community users of the service in the administration of Birth Certificate.Conclusions from this study indicate that the Department of Population and Civil Registration plays an important role in providing maintenance service on the birth certificate Deli Serdang. Factors that affect the service quality Making Birth Certificate at the Department of Population and Civil Registration Deli Serdang are Human Resource, Infrastructure (Facilities) and Public Participation.Keywords: Service, Population Administrasi, and Civil Registartion.